Brain-Machine Interface Closed-loop Bidirectional System Design - Liu, Xilin (Springer International Publishing, 2018)
This book provides an introduction to the emerging area of "Brain-Machine Interfaces," with emphasis on the operation and practical design aspects. The book will help both electrical & bioengineers as well as neuroscience investigators to learn about the next generation brain-machine interfaces. The comprehensive review and design analysis will be very helpful for researchers who are new to this area or interested in the study of the brain. The in-depth discussion of practical design issues especially in animal experiments will also be valuable for experienced researchers. Provides readers with background on brain-machine interfaces, a summary of design requirements, and circuit and system design examples; Presents the first comprehensive study of closed-loop bidirectional BMI's for freely behaving animals; Demonstrates the first reported portable system to provide all necessary hardware for a closed-loop sensorimotor neural interf ace; many innovations in the circuit design optimized for the characteristics of neural interface and electrode-electrolyte interface.